Collinear Stimuli Induce Local and Cross-Areal Coherence in the Visual Cortex of Behaving Monkeys - Gilad, Ariel (Public Library of Science, 2012)
BACKGROUND: Collinear patterns of local visual stimuli are used to study contextual effects in the visual system. Previous studies have shown that proximal collinear flankers, unlike orthogonal, can enhance the detection of a low contrast central element. However, the direct neural interactions between cortical populations processing the individual flanker elements and the central element are largely unknown. METHODOLOGY/PRINCIPAL FINDINGS: Using voltage-sensitive dye imaging (VSDI) we imaged neural population responses in V1 and V2 areas in fixating monkeys while they were presented with collinear or orthogonal arrays of Gabor patches. We then studied the spatio-temporal interactions between neuronal populations processing individual Gabor patches in the two conditions. Time-frequency analysis of the stimulus-evoked VSDI signal showed power increase mainly in low frequencies, i.e., the alpha band (α; 7–14 Hz). Power in the α-band was more discriminative at a single trial level than other neuronal population measures. Importantly, the collinear condition showed an increased intra-areal (V1-V1 and V2-V2) and inter-areal (V1-V2) α-coherence with shorter latencies than the orthogonal condition, both before and after the removal of the stimulus contribution. α-coherence appeared between discrete neural populations processing the individual Gabor patches: the central element and the flankers. CONCLUSIONS/SIGNIFICANCE: Our findings suggest that collinear effects are mediated by synchronization in a distributed network of proximal and distant neuronal populations within and across V1 and V2.